Strategi Penanggulangan Disintegrasi Bangsa: Resolusi Konflik Aceh dan Maluku - Adinda Syifa’us Syauqiyah; Dina Neely Hariyani; Agus Danugroho (Universitas Terbuka, 2024)
This paper attempts to examine the problems of national disintegration that have occurred in Indonesia. Terror acts carried out by GAM and RMS were carried out by the Armed Criminal Group (KKB) through the burning of public buildings and a number of killings. Likewise, efforts to divide the country are also made through publicity through virtual entertainment. If these actions are not resolved immediately, there will be a threat of the disintegration of Papua from Indonesia. This research aims to identify various forms of propaganda for Aceh Merdeka and the Republic of South Maluku. This research uses the descriptive-qualitative method. The results of this study show the use of glittering generalizations and bandwagon techniques in spreading sweet promises and beliefs about referendums and independence. Publicity will be belittled if misleading publicity is not carried out by providing true and accurate information to the public. Therefore, it is very important to provide training and instill a sense of belonging with Indonesia as a way to combat misleading publicity and inappropriateness by KKB GAM and RMS towards the Indonesian people, especially the people of Aceh and Maluku.